2018
DOI: 10.1039/c8ra02727g
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of key aroma compounds in Meilanchun sesame flavor style baijiu by application of aroma extract dilution analysis, quantitative measurements, aroma recombination, and omission/addition experiments

Abstract: The aroma components in Meilanchun sesame flavor style baijiu were identified by aroma extract dilution analysis (AEDA), quantitative analysis, aroma active compound recombination, and omission/addition experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 16 publications
2
38
0
Order By: Relevance
“…Tetramethyl‐pyrazine with an odor activity values ≥1 is an important functional factor in Baijiu , contributing to the roasted sesame‐like aroma . Some reports claim that it is an important flavour compound in Baijiu , while others showed that it had a limited effect . ( z )‐Oxacyclopentadec‐6‐en‐2‐one, which is an essential oil in ambrette seed ( Abelmoschus moschatus ) and in the aerial parts of Piper pierrei , was identified in Daqu for the first time by GC–MS .…”
Section: Resultsmentioning
confidence: 99%
“…Tetramethyl‐pyrazine with an odor activity values ≥1 is an important functional factor in Baijiu , contributing to the roasted sesame‐like aroma . Some reports claim that it is an important flavour compound in Baijiu , while others showed that it had a limited effect . ( z )‐Oxacyclopentadec‐6‐en‐2‐one, which is an essential oil in ambrette seed ( Abelmoschus moschatus ) and in the aerial parts of Piper pierrei , was identified in Daqu for the first time by GC–MS .…”
Section: Resultsmentioning
confidence: 99%
“…Baijiu is a traditional alcoholic beverage with thousands of years of history in China, and it occupies a unique position in Chinese traditional culture as a pearl of ancient Chinese wisdom (Han, 2016;Jin et al, 2017;Sun et al, 2018a;Song et al, 2020). The quality of Baijiu is highly influenced by its special flavor and mouthfeel in the mouth, a determinant factor in acceptance of Baijiu (Fan et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Alcohols, known as fusel alcohols, are the most volatile metabolites synthesized by yeast during alcoholic fermentation (Dzialo et al., 2017). The volatile alcohol in rice wine mainly comes from the fermentation, the conversion of amino acids, and the oxidation of linolenic acid degradation products (Sun et al., 2018). SITCY125 and SITCY601 fermented rice wines had a relatively higher alcohol content of 16,921.01 μg/L (48 hr) and 19,487.52 μg/L (36 hr), respectively.…”
Section: Resultsmentioning
confidence: 99%